Rotenoisin A is a novel anti-adipogenic compound. Issue 1 (1st January 2019) - Cho, Hang-Hee; Park, Hyeon Soo; Jang, Sun-Hee; Won, Chungkil; Kim, Hong-Duck; Kim, Tae Hoon; Cho, Jae-Hyeon
Graphical abstract: Highlights: We investigated the anti-obesity effect of rotenoisin A in 3T3-Ll adipocytes. Rotenoisin A reduced the expression of C/EBPα and PPARγ in 3T3-L1 adipocytes. Rotenoisin A increased AMPK and ACC phosphorylation in 3T3-L1 adipocytes. Rotenoisin A inhibited adipocyte differentiation and adipogenesis in 3T3-L1 cells. Abstract: The purpose of this study was to investigate the mechanisms underlying the inhibitory effects of rotenoisin A on adipogenesis in 3T3-L1 preadipocytes. 3T3-L1 cells were treated with rotenoisin A for 8 days after the induction of differentiation. Oil-red O staining showed that rotenoisin A significantly inhibited DMI-induced lipid accumulation and adipocyte differentiation. We found that rotenoisin A treatment of 3T3-L1 preadipocytes significantly reduced the mRNA and protein levels of the key adipocyte-specific transcription factors C/EBPβ, C/EBPα, and PPARγ and markedly inhibited the expression of fatty acid-binding protein (aP2), fatty acid synthase (FAS), and lipoprotein lipase (LPL). Furthermore, we observed that rotenoisin A substantially increased the phosphorylation of AMP-activated protein kinase (AMPK) and its downstream target phosphorylated acetyl CoA carboxylase (ACC). However, co-treatment with Compound C, an AMPK inhibitor, reversed the rotenoisin A-induced inhibition of the expression of the adipogenic transcription factors C/EBPα and PPARγ and decreased the levels of phosphorylated AMPK in differentiated 3T3-L1 cells. These results demonstrated that the anti-adipogenesis mechanism involves the down-regulation of critical adipogenic transcription factors, including C/EBPβ, C/EBPα, and PPARγ, through activation of the AMPK signaling pathway by rotenoisin A.